Socio-demographic Determinant of Money Script Pattern of Undergraduates of University of Lagos. - Sylvester Ororume Atiri; Similoluwa Titilayo Bello (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2021)
The study tried to determine the money script pattern of undergraduate students of the university of Lagos, with the aim of examining the influence of socio-demographic factors (that is; sex, age, educational level marital status, current socio-economic status and childhood socio-economic status) on their money script pattern. The study involved a cross-sectional survey of 385 undergraduates. One standardized psychological instrument; the Klontz-Money Script Inventory (KMSI), was used to elicit data from the participants. The results show that sex had a significant influence on the money script pattern of two out of the four types of money scripts, that is (Money worship script) F (1,36) = 7.74, P<.05 and (Money status script) F (1,36) = 6.32, P<.05. While the other two had no significant influence on the money script pattern of participants, that is, (Money Avoidance script) F (1,36) = 1.83, P>.05 and (Money vigilance script) F (1,36) = 0.52, P>.05. The other socio-demographic factors; marital status, age, educational level current socio-economic status and childhood socio-economic status did not significantly influence the money script pattern of the participants. The study concluded that the sex of participants to an extent, influences the money script pattern of undergraduates and educational level, marital status, age, current socio-economic and childhood socio-economic status have no influence on the money script pattern of undergraduates.